2020
DOI: 10.3389/fphar.2020.574068
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Suppresses Human Breast Cancer Cell Invasion by Decreasing the Expression of Pituitary Tumor-Transforming Gene 1

Abstract: Statins, or 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors, have been widely used to lower cholesterol and prevent cardiovascular diseases. Recent preclinical and clinical studies have shown that statins exert beneficial effects in the management of breast cancer, while the underlying mechanisms remain to be elucidated. Herein, we sought to investigate the effect of statins on the expression of pituitary tumor-transforming gene 1 (PTTG1), a critical gene involved in human breast cancer invasion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Lovastatin-induced MCF-7 cancer cell death is mediated via the liver kinase B1 (LKB1)-AMP-activated protein kinase (AMPK)-p38 mitogen-activated protein kinase (p38MAPK)-p53-survivin signaling cascade [ 74 ]. Yin et al found that pituitary tumor-transforming gene 1 (PTTG1) was significantly overexpressed in malignant breast cancer cell lines, and simvastatin downregulates its expression by inhibiting GGPP [ 171 ]. Freed-Pastor et al revealed that mutant p53 can disrupt mammary acinar morphology by up-regulating the mevalonate pathway, thereby exerting a carcinogenic effect, while statins inhibit the mevalonate pathway to exert a tumor suppressor effect [ 172 ].…”
Section: Anti-cancer Mechanisms Of Statinsmentioning
confidence: 99%
“…Lovastatin-induced MCF-7 cancer cell death is mediated via the liver kinase B1 (LKB1)-AMP-activated protein kinase (AMPK)-p38 mitogen-activated protein kinase (p38MAPK)-p53-survivin signaling cascade [ 74 ]. Yin et al found that pituitary tumor-transforming gene 1 (PTTG1) was significantly overexpressed in malignant breast cancer cell lines, and simvastatin downregulates its expression by inhibiting GGPP [ 171 ]. Freed-Pastor et al revealed that mutant p53 can disrupt mammary acinar morphology by up-regulating the mevalonate pathway, thereby exerting a carcinogenic effect, while statins inhibit the mevalonate pathway to exert a tumor suppressor effect [ 172 ].…”
Section: Anti-cancer Mechanisms Of Statinsmentioning
confidence: 99%
“…A large number of statins, such as simvastatin, lovastatin and fluvastatin, can inhibit the proliferation and migration of breast cancer. The mechanisms related to their therapeutic effects include inhibition of PI3K/Akt and PPTG1 signaling pathways, activation of LKB1-AMPK-P38MAPK-p53-survivin cascade resulting in cell death, and increased caspase-3-mediated vimentin hydrolysis leading to the death of breast cancer cells (164)(165)(166)(167), indicating that it achieves the purpose of breast cancer treatment by regulating multiple signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Repurposing old drugs for antitumor therapy is an effective and economical way to develop new anticancer drugs. According to their original indications, we summarized these repurposing non-oncology small-molecule drugs for cancer therapy ( Table 1 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , <...>…”
Section: Molecular Mechanisms Repurposing Non-oncology Drugs In Cance...mentioning
confidence: 99%
“…3 , 16 ) and fluvastatin ( Fig. 4 , 17 ) can suppress the PI3K/AKT and RAS/ERK pathways to inhibit cancer 37 , 38 , 124 . Atorvastatin ( Fig.…”
Section: Molecular Mechanisms Repurposing Non-oncology Drugs In Cance...mentioning
confidence: 99%